Pengaruhi Pemberian Pupuk Bokashi Feses Ayam dan Daun Chromolaena Odorata Dengan Level Yang Berbeda (0; 7,5; 15; Dan 22,5 Ton/Ha) Terhadap Pertambahan Panjang Daun, Produksi Berat Segar Dan Komposisi Fraksi Serat Pada Pertumbuhan Ketiga Rumput Odot - Kanjangar, Setiyawan Reku; Sudarma, I Made Adi (Universitas Kristen Wira Wacana Sumba, 2024)
This research was conducted in Kuta Village, Kanatang District, East Sumba Regency. The tools used include drum plates, thermometers, measuring tape, tarpaulin, books, pens, plastic samples, scales and ovens. The materials used are odot grass cuttings, chicken feces bokashi fertilizer and kirinyuh leaves. The experimental design used in this research was a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications and each replication consisted of 9 odot grass cuttings, so there were 144 experimental units. This research is a follow-up research on the growth of three odorata grasses (Pennisetum purpureum Cv. Mott) by applying chicken feces bokashi fertilizer and kirinyuh leaves (Chromolaena odorata) at levels of 0, 7; 5, 15 and 22.5 tonnes/ha. The results of this research show that there is a significant difference in the leaf length variable at 2 weeks of age but not a significant difference at 4-8 weeks of age between odot plants given or without bokashi fertilizer. The research results also showed that there were significant differences in the fresh weight production variable between fertilizer treatment (P1: 731 grams; P2: 732 grams; P3: 736 grams) compared to no fertilizer treatment (P0: 656 grams). The fiber fraction test results showed good results where the average cellulose content was 30.26%; hemicellulose 31.39%; and lignin content is only 3.5%. It was concluded that applying fertilizer up to the level of 7.5 tons/ha was still able to provide good results for odot grass plants in the third growth and harvest.